The association between depressive symptoms and ischemic heart disease in postmenopausal women: a cross-sectional study - Yuan, Yanyan; Chen, Gang (Frontiers in Psychology, 2025)
BackgroundThe negative impact of depression on cardiovascular health has drawn much attention. However, the relationship between depressive symptoms and ischemic heart disease (IHD) in postmenopausal women has not been previously reported.MethodsThis cross-sectional study analyzed data from the National Health and Nutrition Examination Survey (NHANES) spanning 2005 to 2018, including 6,538 postmenopausal women. Weighted multivariable logistic regression analyses were conducted to examine the independent association between depressive symptoms and IHD.ResultsThe fully adjusted model revealed a significant association between depressive symptoms and IHD (OR 1.97, 95% CI [1.24, 3.13]). Subgroup and interaction analyses revealed that depressive symptoms were more strongly linked to IHD risk among younger women, those with lower annual household incomes, non-Hispanic Black women, and individuals with comorbidities such as diabetes and hypercholesterolemia. Moreover, the presence of hypertension moderated the relationship between depressive symptoms and IHD.ConclusionOur findings indicate a significant association between depressive symptoms and increased IHD prevalence among postmenopausal women in the United States, with hypertension acting as a moderating factor. These results offer new insights and potential targets for improving cardiovascular health in this population.